2002
DOI: 10.4024/30603.jbpc.06.03
|View full text |Cite
|
Sign up to set email alerts
|

Nano-assembled thin film gas sensors. I. Ammonia detection by a porphyrin-based multilayer film

Abstract: A thin film of porphyrin deposited by the layer-by-layer method is employed as the active element for an optical sensor. The usefulness of this film technology and the resulting nanoscale matrix for the detection of volatile organic compounds (VOCs), aromatics and amine-containing substances has been studied. The sensing principle is based on monitoring the optical changes of the Q band at 700 nm, as induced by the analyte in the electrostatic interaction between tetrakis(4-sulfophenyl)porphine (TSPP) and poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…Figure 12 shows the absorbance spectrum of the PDDA/SiO2 film after infusion of the TSPP compound. As can be seen from Figure 12, the two Soret bands at wavelengths 419 and 482 nm, along with well-pronounced Q-band at 700 nm, are present, which indicates that the TSPP compound forms J-aggregates in the porous silica film [41,42]. It was previously confirmed that nano-assembled thin films with TSPP in J-aggregate state are particularly sensitive to ammonia gas [42].…”
Section: Employment Of Functional Molecules and Chemical Sensingmentioning
confidence: 65%
See 3 more Smart Citations
“…Figure 12 shows the absorbance spectrum of the PDDA/SiO2 film after infusion of the TSPP compound. As can be seen from Figure 12, the two Soret bands at wavelengths 419 and 482 nm, along with well-pronounced Q-band at 700 nm, are present, which indicates that the TSPP compound forms J-aggregates in the porous silica film [41,42]. It was previously confirmed that nano-assembled thin films with TSPP in J-aggregate state are particularly sensitive to ammonia gas [42].…”
Section: Employment Of Functional Molecules and Chemical Sensingmentioning
confidence: 65%
“…In order to study the stability of the PDDA/SiO2 films infused with TSPP in aqueous solutions, they were immersed into water several times, with the resultant changes in absorption spectra shown in Figure 12. The second Soret-band (482 nm) and Q-band (at 700 nm) disappeared when the film was immersed into water, accompanied by a decrease in the absorbance of the first Soret-band (419 nm), which indicates the partial removal of the adsorbed TSPP molecules from the film [42]. We can speculate that this phenomenon is a result of the cleavage of the J-aggregates of TSPP formed in the space between the SiO2 NPs.…”
Section: Employment Of Functional Molecules and Chemical Sensingmentioning
confidence: 91%
See 2 more Smart Citations
“…Alternatively, the sensor response can be regenerated by rinsing for a few seconds in distilled water. (25) The calibration curve at each wavelength was plotted from the recorded spectra at given ammonia concentrations. The sensor shows linear responses at all wavelengths for a wide concentration range from 0.1 to 20 ppm and the highest sensitivity was observed at 706 nm (Fig.…”
Section: Optical Response To Ammoniamentioning
confidence: 99%